Soil mesofauna in pine forests of the Volga-Kama Reserve - Sukhodolskaya R.A.; Gordienko T. A.; Vavilov D.N.; Shagidullin R.R.; Bakin O.V. (Трансформация экосистем)
The results of studies in soil mesofauna at pine forests of Saraly and Raifa sectors of VolgaKana Reserve are presented in paper. These sectors are located in different landscape zones. The research was conducted in pine forests of the Volga-Kama Natural Biosphere Reserve in 2012–2022. Standard soil-zoological samples were taken in each plot twice a season during three consecutive years. A total of 624 samples were taken and 2870 invertebrates were counted. The taxonomic structure of the mesofauna of both sectors of the Reserve was similar and included 23 and 21 large taxa, in Saraly and Raifa sectors, respectively. Isopodes, Dermaptera and Silphidae were absent in the Raifa sector. The abundance of mesofauna varied approximately within the same limits and averaged 74 specimens per square meter, that was twice as high as the data for the region as a whole. The trophic structure of mesofauna was mostly similar, in all pine forests predators and in most cases saprophages predominated, less phytophages, but they also played the significant role in the pedobiont community. The structure of pedobiont communities differed significantly both in zonal aspect and by the location of the community in a particular.